2022
DOI: 10.3390/cimb44070200
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Infections of The Central Nervous System Have Lowered Gut Microbiota Alpha Diversity

Abstract: There are multiple lines of evidence for the existence of communication between the central nervous system (CNS), gut, and intestinal microbiome. Despite extensive analysis conducted on various neurological disorders, the gut microbiome was not yet analyzed in neuroinfections. In the current study, we analyzed the gut microbiome in 47 consecutive patients hospitalized with neuroinfection (26 patients had viral encephalitis/meningitis; 8 patients had bacterial meningitis) and in 20 matched for age and gender he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…GIM diversity metrics are being applied in CNS disorders as discussed in previous sections. However, barring one recent report, there is a lacuna regarding GIM diversity in the field of viral neuropathology. In addition, the molecular mechanisms of the major metabolites acetate, propionate, and butyrate appear to be converging despite the variety in disease phenotypes (Table ).…”
Section: Future Directions In Virologymentioning
confidence: 99%
See 1 more Smart Citation
“…GIM diversity metrics are being applied in CNS disorders as discussed in previous sections. However, barring one recent report, there is a lacuna regarding GIM diversity in the field of viral neuropathology. In addition, the molecular mechanisms of the major metabolites acetate, propionate, and butyrate appear to be converging despite the variety in disease phenotypes (Table ).…”
Section: Future Directions In Virologymentioning
confidence: 99%
“…Technologies such as 16S rRNA sequencing and shotgun metagenomic sequencing have enabled the study of the composition of GI microbiome and variations of this composition among individual host organisms. ,, α- (within sample) and β- and γ-diversity (between two samples) metrics reflect similarities and/or differences in the “core” microbial composition of the GI habitat in health and disease contexts. Microbial diversity exploration in CNS disorders has also begun. A few pioneering studies began investigating the impact of GIM on neurochemistry, where changes in the microbiota led to changes in behavior and neurochemical mediators in animal models. Heijtz et al demonstrated that early life microbiota exposure (within the first 6 weeks) had life-long behavioral and brain developmental impact.…”
Section: Routes Of Gut–brain Communicationmentioning
confidence: 99%
“…Nanomaterials can pass through biological barriers, circulate through vessels, and disrupt the permeability of biological membranes and cell walls [74]. Several studies have demonstrated that nanomaterials can cause dysbiosis in the gut microbiota, contributing to various primary health conditions [75]. The toxic effects of nanomaterials on living systems depend on various factors, including the chemical composition of the nanomaterials, the physical shape, size, route of exposure (such as oral, intravenous, nasal), dosage, and duration of exposure [76].…”
Section: Nanoparticle Uptake and Toxic Effects On Bifidobacteriummentioning
confidence: 99%
“…The intricate relationship between gut microbiota and the central nervous system (CNS) has garnered significant attention due to its link with various neurological and cognitive disorders [75]. This interaction occurs through three primary routes.…”
Section: Nanoparticle-encapsulated Bifidobacterium In Alzheimer's Dis...mentioning
confidence: 99%
“…In addition, research showed the correlation between the changed gut microbiota and clinical phenotype [11]. Meanwhile, it has been showed that changed ora are associated with the onset and progression of ABI and BM [5,10]. Seki, et al found Klebsiella may as an outstanding predictor indicator of brain injury in preterm infants [12].…”
Section: Introductionmentioning
confidence: 99%